Evaluación de la fibrosidad sensorial a diferentes alturas de corte del turión de espárrago verde en conserva (Asparagus officinalis L.) - Silva Chuquipoma, Diego Honorato (2019)
ABSTRACT The objective of the investigation was to determine the cutting height of canned green asparagus (Asparagus officinalis L.) to reduce sensory fibrousness. 30 samples of asparagus spears of calibers 4, 5, 6 y 7 mm, 10 cm in length was measured from the base to the tip of the spear and cuts were made every 1 cm to evaluate the instrumental cutting force (N) and sensory fibrousness through a trained internal panel formed by 8 people; Likewise, the Cut-off Point methodology was applied to determine the appropriate height at which the spear should be cut to reduce sensory fibrousness. The results showed that there were no significant differences in cutting force for the different calibers used, on the other hand, the results of sensory evaluation and instrumental texture evaluation (cutting force) showed a high correlation between them (R2 = 0.9248). Finally, it was concluded that the cutting height was 2.69 cm with a coefficient of determination R2 of 0.9059, indicating that there is a greater detectable sensory fibrousness in the first 3 centimeters of the base of the spear.